Roles of foods and related components: an overview on cancer causatives, and plausible preventions - Hamdoon A. Mohammed; Ghassan M. Sulaiman; Ali Z. Al-Saffar; Mosleh M. Abomughaid; Nehia N. Hussein; Zeina T. Salih; Noora A. Hadi; Mayyadah H. Mohsin; Hayder M. Al-kuraishy; Riaz A. Khan; Ahmed Ismail (Applied Food Research)
Cancer, a complex and frequently fatal disease category, is recognized as the leading cause of death worldwide. Growing evidence suggests that nutrition plays an important bidirectional role in cancer prognosis. With food components acting as both carcinogenic initiators and preventative agents, the relationship between diet and carcinogenesis involves complex and multifaceted interactions in the biochemical makeup of living things. Diets high in processed red meat, refined sugars, and harmful fats, particularly those from Western countries, have been linked to an increase in cancer. Diets high in whole grains, fruits, vegetables, and healthy fats, on the other hand, have been shown to be cancer-protective. The interaction of nutritional components in foods has an impact on fundamental physiological and biochemical processes such as oxidative stress, immune response, and inflammation. These molecular physio-biochemical interactions, as part of the critical biomechanistic dynamics, shift or create complex pathways that either promote or inhibit cancer development. The current review examines the contrasting roles of foods in cancer biology, specifically the mechanisms by which food-related carcinogens and anticarcinogens function. It also examines the impact of specific dietary components on cancer risk and suggests practical dietary patterns for cancer prevention and management. Understanding the dynamic relationships between foods and diseases allows for more informed decision-making and implementation at both the individual and population levels, potentially lowering cancer risk, management costs, and the burden on healthcare systems. As a result, evidence-based nutritional interventions and strategies can help to prevent and treat cancer.